Thermal diffusivity analysis of doped poly(methyl-methacrylate) with electron donor and acceptor molecules - Cornelio, M. L.; Toma, M. M. (Pion Ltd, 1999)
A computer-assisted method for analysing photoacoustic spectra has been developed in the Windows(TM) environment with the use of an easy graphical interface, the computer simulation was carried out with the aim of using the entire expression of the Rosencwaig-Gersho theory, thus permitting multiple applications. The simulation was applied to a system that mimics the electron transfer process in which the concentration of octaethylporphin donor molecules was constant whereas the concentration of duroquinone and 2,3-dichloro-5,6-dicyano-1, l-benzoquinone acceptor molecules varied. The increment of the acceptor concentration influenced the photoacoustic amplitude and phase signals. In the phase signal a significant shift to smaller values was observed, denoting a faster heat generation. The analysis of the photoacoustic signal enabled the determination of the thermal diffusivity, the result obtained through the simulation was about (7 +/- 1) x 10(-7) m(2) s(-1) indicating that changes in the photoacoustic phase signals were due to the electron transfer process rather than changes in the thermal properties of the sample.